From silver to platinum: The effect of frequent flier tier levels on airline demand - Christiaan Behrens; Gerben de Jong; Jos van Ommeren (Tinbergen Institute, 2021)
How do customer loyalty programs create switching costs? We estimate the demand effects of tier levels within a frequent flier program by exploiting discrete tier thresholds. We have two main results. First, members increase demand to reach a higher tier level just before the end of the calendar year when tier levels are determined, but do not manipulate demand in the months before. Second, using a fuzzy regression discontinuity design with running variables from earlier months, we show that upgraded members further increase their demand to enjoy the tier level benefits. Both effects are increasing in tier level. These findings are consistent with economic theories which point out that loyalty programs aim to create convex switching costs.
Keywords: 330; customer loyalty; switching costs; frequent flier program; fuzzy regression discontinuity; manipulated running variables